Optimal Use of Ganciclovir and Valganciclovir in Transplanted Patients: How Does It Relate to the Outcome? - Mozaffar, Maryam; Shahidi, Shahrzad; Mansourian, Marjan; Badri, Shirinsadat (Journal of Transplantation, 2018)
Objective. Organ transplant recipients receive immunosuppressive regimens to prevent transplant rejection, which put them at increased risk for opportunistic infections like cytomegalovirus (CMV). Ganciclovir and Valganciclovir are mostly used to prevent or treat CMV. Any incorrect use of the drug may have serious consequences for patients. In this study, the outcome of transplant recipients was assessed in relation to the optimal or suboptimal use of Ganciclovir or Valganciclovir. Methods. This study was performed on 148 hospitalized patients who received Ganciclovir or Valganciclovir in the nephrology and kidney transplantation departments of our university hospitals, from March 2012 to December 2016. Patients’ demographic and clinical data including dose and duration of treatment were collected and then analyzed in comparison with the standard CMV treatment protocols. Findings. About 94.6% of patients received Ganciclovir or Valganciclovir therapy consistent with the standard defined indications. The mean ratio of prescribed daily dose to the optimal dose was 2.9 in the first dose, 2.0 in the second dose, 1.3 in the third dose, and 1.5 in the fourth dose. From 148 included patients, 26.5% experienced CMV infection once, 7.2% experienced CMV infection twice, and 1.2% had CMV infection for 3 times, within six-month follow-up after first episode of antiviral therapy during hospitalization. Conclusion. In this study, empiric anti-CMV therapy was initially given. The doses used were generally higher than recommended but we could not find more adverse events in the patients receiving high initial doses. In any case, it seems necessary to advocate use of standard treatment guidelines to avoid adverse outcomes.